Daya tarik pembelian produk kosmetik di Shopee: Peran ulasan, label halal, harga, dan kualitas pelayanan dengan kategori produk sebagai pemoderator - Safitri, Hilda; Pratama, Abdul Aziz (Journal of Halal Industry Studies, 2024)
This study aims to analyze the influence of product reviews, halal labels, prices, and service quality with product categories as moderating variables on purchasing decisions for cosmetic products on Shopee. The objectives of this study are product reviews, halal labels, prices, service quality, product categories, and Purchasing Decisions. The research was conducted in a quantitative descriptive study using data collection techniques through the distribution of questionnaires or surveys using Google Forms—distributed questionnaires to users of online shopping services, namely Shopee. The type of sample uses non-probability sampling. The data type used is primary data obtained directly from the studied object. The data analysis technique uses Moderated Regression Analysis (MRA). The study results show that the variables of product reviews, prices, and service quality have a positive and significant effect on purchasing decisions, and the presence of product categories as moderators strengthens this influence. While the halal label variable does not have a positive and significant impact on buying decisions, moderating variables further weaken the influence of the halal label.